Single-cell RNA sequencing analysis of lung cells in COVID-19 patients with diabetes, hypertension, and comorbid diabetes-hypertension - Zhang, Xin; Deng, Xiaoqian; Zhang, Liangliang; Wang, Pengbo; Tong, Xia; Mo, Yan; Zhang, Yuansheng; Zhang, Yan; Mo, Chunheng; Zhang, Lanlan (Frontiers in Endocrinology, 2023)
Background: There is growing evidence that the lung is a target organ for injury in diabetes and hypertension. There are no studies on the status of the lungs, especially cellular subpopulations, and related functions in patients with diabetes, hypertension, and hypertension-diabetes after combined SARS-CoV-2 infection.Method: Using single-cell meta-analysis in combination with bulk-seq analysis, we identified three drug targets and potential receptors for SARS-CoV-2 infection in lung tissues from patients with diabetes, hypertension, and hypertension-diabetes, referred to as "co-morbid" patients. Using single-cell meta-analysis analysis in combination with bulk-seq, we identified drug targets and potential receptors for SARS-CoV-2 infection in the three co-morbidities.The single-cell meta-analysis of lung samples from SARS-CoV-2-infected individuals with diabetes, hypertension, and hypertension-diabetes comorbidity revealed an upregulation of fibroblast subpopulations in these disease conditions associated with a predictive decrease in lung function. To further investigate the response of fibroblasts to therapeutic targets in hypertension and diabetes, we analyzed 35 upregulated targets in both diabetes and hypertension.Interestingly, among these targets, five specific genes were upregulated in fibroblasts, suggesting their potential association with enhanced activation of endothelial cells. Furthermore, our investigation into the underlying mechanisms driving fibroblast upregulation indicated that KREMEN1, rather than ACE2, could be the receptor responsible for fibroblast activation. This finding adds novel insights into the molecular processes involved in fibroblast modulation in the context of SARS-CoV-2 infection within these comorbid conditions. Lastly, we compared the efficacy of Pirfenidone and Nintedanib as therapeutic interventions targeting fibroblasts prone to pulmonary fibrosis. Our findings suggest that Nintedanib may be a more suitable treatment option for COVID-19 patients with diabetes and hypertension who exhibit fibrotic lung lesions.In the context of SARS-CoV-2 infections, diabetes, hypertension, and their coexistence predominantly lead to myofibroblast proliferation. This phenomenon could be attributed to the upregulation of activated endothelial cells. Moreover, it is noteworthy that therapeutic interventions targeting hypertension-diabetes demonstrate superior efficacy. Regarding treating fibrotic lung conditions, Nintedanib is a more compelling therapeutic option.